Effects of Beam Conditions in Ground Irradiation Tests on Degradation of Photovoltaic Characteristics of Space Solar Cells - Mitsuru Imaizumi; Takeshi Ohshima; Yosuke Yuri; Kohtaku Suzuki; Yoshifumi Ito (Quantum Beam Science, 2021)
We investigated the effects of irradiation beam conditions on the performance degradation of silicon and triple-junction solar cells for use in space. The fluence rates of electron and proton beams were varied. Degradation did not depend on the fluence rate of protons for both cells. A higher fluence rate of electrons caused greater degradation of the Si cell, but the dependence was due to the temperature increase during irradiation. Two beam-area expansion methods, defocusing and scanning, were examined for proton irradiation of various energies (50 keV–10 MeV). In comparing the output degradation from irradiation with defocused and scanned proton beams, no significant difference in degradation was found for any proton energy. We plan to reflect these findings into ISO standard of irradiation test method of space solar cells.